Diseño de una política de seguridad de la información para la Dirección de Tecnologías de la Información de la Universidad Técnica de Cotopaxi, basado en la Norma ISO 2700. - Álvarez Marcalla, Williams Manuel (2021)
The information systems evolution requires the emergence of professionals in IT area responsible to evaluate their correct operation, detecting those weak points that require preventive and corrective measures to avoid loss of information that could cause significant costs to organizations. At present, institutions are exposed not only to material theft or assaults on their facilities, but also to computer security crimes that can affect the organization of data and relevant information. The purpose of this research project is to design an information security policy for the University, which needs to have security and provide sufficient support to protect the information of the institution. The design of computer security policies will allow to minimize risks and threats that may compromise the correct use of computer resources such as information, processes, systems and networks. For this, ISO / IEC 27000 Standard was used, which seeks information, confidentiality, integrity and availability.